Pelatihan Pembuatan Paper Soap Berbahan Daun Kelor dan Promosi kesehatan Kepada PKK Perumahan - Indah Yunitasari; Dwi Swastanti Ridianingsih; Nurul Hidayah; Krisno Punto (IKIP PGRI Bojonegoro, 2023)
ABSTRACTMultiliteracy-based training, which combines the scientific dimensions of science and health. The purpose of this community service is to make paper soap from moringa leaves and promote health. This activity is important to carry out in order to broaden residents' insights in responding to the challenges of the post-pandemic coronavirus, optimize opportunities for utilizing Moringa leaves, and simultaneously package it as a health promotion effort. There were 20 participants from the Sukomaju Asri Residential PKK who took part in the activity and participated actively. The implementation of this community service goes through several stages, namely: designing activity schemes, licensing, outreach, making paper soap, and giving feedback to training participants. The result is that 90% of the trainees know the importance of washing soap using running water, and 50% of the trainees understand the steps to wash their hands properly before conducting the training. 85% of the trainees have never heard of paper soap; 75% of the trainees already know the benefits of Moringa leaves, which can kill bacteria; and after training, 90% of participants can apply paper soap making techniques. Participants understand the post-pandemic health paradigm change, which shows a figure of 85%. 70% of participants understood how to carry out early detection and self-protection in cases of COVID-19. ABSTRAKPelatihan berbasis multiliterasi, yang menggabungkan dimensi keilmuan sains dan kesehatan. Tujuan dari pengabdian kepada masyarakat ini adalah untuk membuat paper soap berbahan dasar daun kelor dan promosi kesehatan. Kegiatan ini penting dilakukan dalam rangka membuka wawasan warga dalam menjawab tantangan pasca pandemic virus korona, mengoptimalkan peluang-peluang pemanfaatan daun kelor, lalu secara simultan dikemas sebagai upaya promosi kesehatan. Terdapat 20 peserta dari PKK Perumahan Sukomaju Asri yang mengikuti kegiatan dan berpartisipasi secara aktif. Penyelenggaraan pengabdian kepada masyarakat ini melalui beberapa tahapan, yaitu: perancangan skema kegiatan, perizinan, sosialisasi, pembuatan paper soap, serta yang terakhir adalah pemberian umpan balik kepada peserta pelatihan. Hasilnya 90% peserta pelatihan mengetahui pentingnya mencuci sabun dengan menggunakan air mengalir, 50% peserta pelatihan memahami langkah-langkah mencuci tangan dengan benar, sebelum melakukan pelatihan 85% peserta pelatihan belum pernah mendengar paper soap, 75% peserta pelatihan sudah mengetahui manfaat dari daun kelor yang dapat membunuh bakteri, dan setelah pelatihan 90% peserta dapat menerapkan pembuatan paper soap atau sabun kertas. Peserta memahami perubahan paradigma kesehatan pasca pandemic yang menunjukkan angka 85%. Sebesar 70% peserta memahami bagaimana cara melakukan deteksi dini dan proteksi diri pada kasus Covid-19.